(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the relationship between green economy principles and sustainable development with a focus on economic efficiency factors. The study analyzes resource efficiency, environmental sustainability, energy efficiency, and the role of innovation. The findings highlight the key determinants of economic efficiency in the transition toward a green economy.